2008
DOI: 10.1111/j.1442-9071.2008.01793.x
|View full text |Cite
|
Sign up to set email alerts
|

Components of the fibrinolytic system in the vitreous body in patients with vitreoretinal disorders

Abstract: Purpose:  To assess components of the fibrinolytic system in the vitreous humour and serum of patients with vitreoretinal disorders. Methods:  Forty‐three samples of vitreous humour and plasma of 43 patients undergoing pars plana vitrectomy for macular hole, macular pucker, retinal detachment or proliferative vitreoretinopathy were evaluated for their content of plasminogen, a2‐antiplasmin, plasminogen‐activator‐inhibitor 1, plasmin‐a2‐antiplasmin‐complex, tissue plasminogen activator, total protein, albumin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…To the best of our knowledge, studies on intravitreal plasminogen activity in patients with CRVO have not been published so far. Ulrich et al [62] were not able to detect any plasminogen activity in vitreous samples in patients with and without BRB breakdown. In contrast, Esser et al [63] found a significant increase in vitreous plasminogen activities in patients with proliferative (diabetic) vitreoretinopathy (0.108-0.142 mg/ml; about 100%N) with a consecutive BRB breakdown in comparison to healthy controls (0.015 mg/ml; about 1%N), and plasminogen activities were correlated with the severity of diabetic vitreoretinal damage.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, studies on intravitreal plasminogen activity in patients with CRVO have not been published so far. Ulrich et al [62] were not able to detect any plasminogen activity in vitreous samples in patients with and without BRB breakdown. In contrast, Esser et al [63] found a significant increase in vitreous plasminogen activities in patients with proliferative (diabetic) vitreoretinopathy (0.108-0.142 mg/ml; about 100%N) with a consecutive BRB breakdown in comparison to healthy controls (0.015 mg/ml; about 1%N), and plasminogen activities were correlated with the severity of diabetic vitreoretinal damage.…”
Section: Discussionmentioning
confidence: 99%
“…4,14,20,21 The average amount of APE obtained and injected in this method was 0.21 IU/0.2 mL (1.05 ± 0.12 IU/mL), but this dose was suffi cient to induce a complete vitreous detachment in the patients in this study. A recent article shows high intravitreal plasminogen levels in diabetic eyes, 22 so what we cannot be sure is if all the and control eye CMTs were 241.81 ± 47.9 μm and 530.375 ± 85.33 μm, respectively. There was a statistically significant difference (P < 0.001, bilateral Wilcoxon test for paired samples) between both groups.…”
Section: Discussionmentioning
confidence: 96%
“…Fibrinogen is known as a positive acute phase reactant. Histological examination of subretinal strands after RRD and immunostaining of early preretinal exudates and recently the increased level of fibrinolytic components in the vitreous, indicate fibrin/fibrinogen presence in eyes suffering with retinal detachment 911. Specific binding with collagen type IV is an additional significant observation 12.…”
Section: Discussionmentioning
confidence: 98%